Relationships between self- directed learning, leadership of head nurse and performance of nurse anesthetists, General hospitals, Ministry of Public Health - สุนทร, ทัศนีย์; ประจุศิลป, กัญญดา (Journal of The Royal Thai Army Nurses, 2018)
The purpose of this discriptive research was to study the relationships between self- directed learning, leadership of head nurse and performance of nurse anesthetists, General hospitals, Ministry of Public Health. The sample were 278 nurse anesthetists in the General hospitals, Ministry of Public Health, selected by simple random sampling technique. The research instruments were personalfactors, self directed learning, leadership of head nurse and performance of nurse anesthetists questionnaires. All questionnaires were tested for content validity and reliability with Cronbach's alpha coefficients of .83, .96 and .91 respectively. Data were analyzed by frequency, percentage, mean, standard deviation and Pearson’s product moment correlation coefficient. The major findings were as follows: 1. Mean score of performance of nurse anesthetists was at the high level. ( = 4.43, SD = .43) 2. Mean score of self directed learning was at the high level. ( = 3.77, SD = .48), leadership of head nurse was at the high level. ( = 3.68, SD = .54) 3. There was positively significant relationship between self directed learning, leadership of head nurse, and performance of nurse anesthetists at the .05 level. (r= .32 and .44 respectively)